Adopsi Life Cycle Costing Untuk Bangunan Gedung Diklat Muara Enim - KAMING, Peter; LIANO, Ign. Himawan; SIGIT, W. Alexander (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2019)
Both initial cost for construction and future costs for operation and maintenance of buildings are very important that must be considered by the building owner. Therefore, estimating Life Cycle Cost (LCC) in long term is a must in determining the amount of money spent for the building projects. The objective of this study is to apply a method for LCC to estimate overall costs starting from initial, maintenance, and operational costs. In this study, the LCC also incorporated inflation and bank interest rates in long-term perspective. In this study, LCC was implemented in a building that functioned as a training facility in a building complex in the Muara Enim District. Southern Sumatera. By using the LCC method for estimating cost for a period of 25 years, result shows that the proportion initial cost of construction is 39.12%, maintenance and replacement cost is 16.28%; and operational cost is 44.61%.